2011
DOI: 10.1093/neuonc/nor203
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid interleukin-10 is a potentially useful biomarker in immunocompetent primary central nervous system lymphoma (PCNSL)

Abstract: The diagnosis of primary central nervous system lymphoma (PCNSL) by radiographical examination is often difficult because of its similarity to other brain tumors. To test whether interleukin-10 (IL-10) and IL-6 can be used to distinguish PCNSL from other brain tumors that are radiographically similar, cerebrospinal fluid (CSF) levels of IL-10 and IL-6 were measured in 66 patients with intracranial tumors (PCNSLs: 26 cases; other brain tumors: 40 cases). In the patients with PCNSLs, the median CSF levels of IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
101
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 41 publications
6
101
3
3
Order By: Relevance
“…MRI does not have a high specificity for distinguishing PCNSL from glioma and metastatic brain tumors39, 40 and often results in misdiagnosis 6, 8, 9. In the present study, the sensitivity of MRI for the diagnosis of PCNSL was 52.4% (11/21), whereas the sensitivity of CSF Npt concentration for the diagnosis of PCNSL was 90% (9/10) in the 10 false‐negative PCNSL cases.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…MRI does not have a high specificity for distinguishing PCNSL from glioma and metastatic brain tumors39, 40 and often results in misdiagnosis 6, 8, 9. In the present study, the sensitivity of MRI for the diagnosis of PCNSL was 52.4% (11/21), whereas the sensitivity of CSF Npt concentration for the diagnosis of PCNSL was 90% (9/10) in the 10 false‐negative PCNSL cases.…”
Section: Discussioncontrasting
confidence: 48%
“…Magnetic resonance imaging (MRI), especially contrast‐enhanced MRI, is the method of choice for the detection of PCNSL. However, as PCNSL does not have a characteristic radiological feature, misdiagnosis is not uncommon,6, 8, 9 and the differential diagnosis of PCNSL from other brain tumors such as meningioma, glioma, and metastatic brain tumors and some inflammatory diseases such as sarcoidosis and multiple sclerosis is typically challenging 8. Indeed, correct diagnosis of an atypical focal brain lesion based solely on radiological examination is a formidable challenge.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with previous observations regarding the relationship between elevated IL-10 levels and adverse outcome in DLBCL. 14,29 Moreover, serial analysis demonstrated that CSF IL-10 concentration within the lumbar sac and in the brain ventricle reproducibly correlated with clinical course, both at diagnosis and in PCNSL and SCNSL patients at relapse. CSF levels of IL-10 also correlated with clinical response or progression in CNS lymphoma patients who participated in a phase 1 trial of intraventricular rituximab plus methotrexate.…”
mentioning
confidence: 93%
“…13 Candidate peptides hypothesized to have a role in the pathogenesis of CNS lymphomas have also been evaluated in preliminary studies, including interleukin (IL)-10, also identified using proteomic methods, 13 and the CXC chemokine ligand (CXCL)13, a mediator of B-cell migration. Recently, Sasayama et al 14 found elevated IL-10 in CSF specimens from 31 immunocompetent patients with PCNSL compared with 59 patients with other types of brain tumors, mainly malignant gliomas. Fischer et al 15 detected elevated CXCL13 concentration in CSF from 30 lymphoma patients relative to 40 control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with intracranial tumors, the levels of IL-10 in the CSF have been found to be significantly higher in those with PCNSLs than in those with other brain tumors (9). However, the utility of the IL-10 levels in CSF for identifying LC has not been clarified.…”
Section: Introductionmentioning
confidence: 99%